2004
DOI: 10.1080/10400435.2004.10132073
|View full text |Cite
|
Sign up to set email alerts
|

Using Telerehabilitation to Identify Home Modification Needs

Abstract: Teleconferencing technology has great potential for providing cost-effective in-home assessment for home modification services from anywhere to anyone in need. Despite its enormous potential, the use of this technology as a means to deliver these specific services had not been investigated. This project investigated the use of televideo technology to provide remote home assessment services to patients prior to discharge so that they could function as independently as possible in their own homes after being dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…23 A number of studies in various care settings illustrate the ability to provide clinical care or augment traditional in-home care through telerehabilitation for varied patient populations. [24][25][26][27][28][29][30][31][32][33][34][35] …”
Section: Introductionmentioning
confidence: 99%
“…23 A number of studies in various care settings illustrate the ability to provide clinical care or augment traditional in-home care through telerehabilitation for varied patient populations. [24][25][26][27][28][29][30][31][32][33][34][35] …”
Section: Introductionmentioning
confidence: 99%
“…The videoconferencing system we used in this clinical trial was developed for a previous study on providing remote home assessments [21] and tailored for this project to allow live two-way video and audio patienttherapist interaction. The system consisted of "off-theshelf" technology that used POTS lines, which are located in virtually all homes in the United States.…”
Section: Equipmentmentioning
confidence: 99%
“…Two additional studies demonstrated that videoconferencing technology could be used successfully for developing home-modification recommendations and that videoconferencing equipment produced images sufficient for visualizing and assessing all but fine motor movements (resolution sufficient for therapists at a remote location to determine space measurements in a home with 1/4 in. accuracy) [21][22].…”
Section: Literature Review Teletechnologymentioning
confidence: 99%
“…First, the participants were asked to look at and comment on screen shots of several websites (Figs 2 and 3). Moreover, work by other researchers regarding websites for older people, the digital provision of in-home assessments for home modification services, and communication practices for people with dementia were consulted [20][21][22][23]. Notes and observations from this first session were used to develop the topics of the second session.…”
Section: Consultation Roundsmentioning
confidence: 99%